What happens when they think they are right? Error awareness analysis of sentence comprehension deficits in aphasia. Issue 12 (2nd December 2018) - Arantzeta, Miren; Webster, Janet; Laka, Itziar; Martínez-Zabaleta, Maite; Howard, David
ABSTRACT: Background : Comprehension of non-canonical sentences is frequently characterised by chance level performance in people with aphasia (PWA). Chance level performance has been interpreted as guessing, but online data does not support this rendering. It is still not clear whether the incorrect sentence processing is guided by the compensatory strategies that PWA might employ to overcome linguistic difficulties. Aims: We aim to study to what extent people with non-fluent aphasia are aware of their sentence comprehension deficits. Methods & Procedures : This study combined offline and online data to investigate the effect of word order and error-awareness on sentence comprehension in a group of PWA and non-brain damaged (NBD) participants. The offline tasks involved auditory sentence picture-matching immediately followed by a confidence rating (CR). Participants were asked to judge the perceived correctness of their previous answer. Online data consisted of eye-tracking. Outcomes & Results : Replicating previous findings, PWA had significantly worse comprehension of Theme-Agent order compared to Agent-Theme order sentences. Controls showed ceiling level sentence comprehension. CR was a poor predictor of response accuracy in PWA, but moderate-good in NBD. A total of 6.8% of judgements were classified as "guessing" by PWA. Post hoc gaze data analysis indicated that CR was a predictor of the fixation pattern during the presentation of the linguistic stimuli. Conclusions : Results suggest that PWA were mostly unaware of their sentence comprehension errors and did not consciously employ strategies to compensate for their difficulties.